Mortality from malignant cervical cancer in Maranhão state: epidemiological profile and trend (Research, Society and Development, 2020)
This study is a research model with exploratory, epidemiological and descriptive analysis with cross-sectional, quantitative and retrospective approach, through searching the secondary database, regarding the prevalence of cervical cancer in the state of Maranhão among the 2008 to 2017. Thus, this study aimed to characterize the epidemiological profile, the analysis of the most common age range of the onset of pathological manifestations, as well as to determine the occurrence of morbidity and mortality in individuals with cervical cancer. Regarding results, the data show that it was possible to identify a significant trend of deaths from malignant cervical cancer in the state of Maranhão, in women under 60 years of race / brown color, especially in 2017. Among deaths, it was observed the highest proportion of deaths occurred in hospitals, about 2143 cases. Followed by deaths at home, totaling 881 occurrences. It is noted that the epidemiological profile of cervical cancer occurs at high rates. Therefore, there is a need to improve public health completely, with emphasis on women's health programs, as well as making them aware of seeking access to services of health.